Determining clinically meaningful thresholds for the hip outcome score sport-specific subscale in athletes undergoing hip arthroscopy for femoroacetabular impingement syndrome - Owens, J. S.; Jimenez, A. E.; Lee, M. S.; George, T.; Maldonado, D. R.; Domb, B. G. (The American Journal of Sports Medicine, 2022)
Background: The minimal clinically important difference (MCID), Patient Acceptable Symptom State (PASS), substantial clinical benefit (SCB), and maximum outcome improvement (MOI) satisfaction threshold for the Hip Outcome Score Sport-Specific Subscale (HOS-SSS) have not been established in athletes undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS).